AKTIVITAS ENZIM 2,4-D MONOOKSIGENASE DARI BERBAGAI MIKROBA - Nunik Sulistinah (BERITA BIOLOGI, 1999)
Nine cultures both from fungi and bacteria have been selected for testing their 2,4-D monooxygenase activity to degrade 2,4-Dtohlorophenoxyacetic acid (2,4-D). The results showed that all the cultures which were tested grows at 1000 ppm 2,4-D. Three cultures (Trichoderma viride. Asperoillus niqer and Isolat E (unidentified)) of the nine cultures are able to grow at 4000 ppm. T. viride grows well on Minimal Basal Media which contained glucose and 2000 ppm 2,4-D and produced the highest biomass (0.8660 g/l) than the others. The biomass of T. viride grew on MBM (without glucose) and added with 2000 ppm 2,4-D is 0,6520g/l. This indicated that the culture is tolerant to 2,4-D and able to use 2,4-D compound as energy and carbon sources for its growth. But we failed to prove the 2,4-D monooxygenase activity of supernatant of T. viride by measuring the changing of pH-value in the 2,4-D breakdown reaction.